High Rate and Long Cycle Life of a CNT/rGO/Si Nanoparticle Composite Anode for Lithium‐Ion Batteries. (25th July 2017) - Wang, Sizhe; Liao, Jiaxuan; Wu, Mengqiang; Xu, Ziqiang; Gong, Feng; Chen, Cheng; Wang, Yuesheng; Yan, Xingbin
Abstract: Si nanoparticle (Si‐NP) composite anode with high rate and long cycle life is an attractive anode material for lithium‐ion battery (LIB) in hybrid electric vehicle (HEV)/pure electric vehicle (PEV). In this work, a carbon nanotube (CNT)/reduced graphene oxide (rGO)/Si nanoparticle composite with alternated structure as Li‐ion battery anode is prepared. In this structure, rGO completely wraps the entire Si/CNT networks by different layers and CNT networks provide fast electron transport pathways with reduced solid‐state diffusion, so that the stable solid‐electrolyte interphase layer can form on the whole surface of the matrix instead of on single Si nanoparticle, which ensure the high cycle stability to achieve the excellent cycle performance. As a result, the CNT/rGO/Si‐NP anode exhibits high performances with long cycle life (≈455 mAh g −1 at 15 A g −1 after 2000 cycles), high specific charge capacity (≈2250 mAh g −1 at 0.2 A g −1, ≈650 mAh g −1 at 15 A g −1 ), and fast charge/discharge rates (up to 16 A g −1 ). This nanostructure anode with facile and low‐cost synthesis method, as well as excellent electrochemical performances, makes it attractive for the long life cycles at high rate of the next generation LIB applications in HEV/PEV. Abstract : A carbon nanotube (CNT)/reduced graphene oxide/Si‐nanoparticle composite of alternated structure anode is developed. CNT networks provide fast electron transport pathways with reduced solid‐state diffusion to form stable solid‐electrolyte interphase. The composite anode exhibits high rate capability and long cycle life for application of lithium‐ion batteries in hybrid electric vehicle/pure electric vehicle.